2021
DOI: 10.3390/polym13111865
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Polymeric Material Utilising Sustainable Radiation Curable Palm Oil-Based Products for Advanced Technology Applications

Abstract: In countries that are rich with oil palm, the use of palm oil to produce bio-based acrylates and polyol can be the most eminent raw materials used for developing new and advanced natural polymeric materials involving radiation technique, like coating resins, nanoparticles, scaffold, nanocomposites, and lithography for different branches of the industry. The presence of hydrocarbon chains, carbon double bonds, and ester bonds in palm oil allows it to open up the possibility of fine-tuning its unique structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…9 Vegetable oil is a potentially renewable feedstock for a range of industrial or consumer goods, as well as a source of bioresin, and it adheres to the seventh of the 12 principles of green chemistry, which promotes chemistry's sustainability. 10,11 More recently, vegetable oils have come to prominence as an alternative source for products, such as polymers, that have primarily been derived from petroleum, 12 such as those based on soybean, 1,13,14 linseed, 15,16 castor, 17 canola, 18 palm, 19 safflower 20 and corn oil. 21 The addition of some functional vegetable oils, such as epoxidized corn oil (ECO), can potentially improve the extrinsic and intrinsic properties of ER, while also increasing the biobased content of the final composites.…”
Section: Introductionmentioning
confidence: 99%
“…9 Vegetable oil is a potentially renewable feedstock for a range of industrial or consumer goods, as well as a source of bioresin, and it adheres to the seventh of the 12 principles of green chemistry, which promotes chemistry's sustainability. 10,11 More recently, vegetable oils have come to prominence as an alternative source for products, such as polymers, that have primarily been derived from petroleum, 12 such as those based on soybean, 1,13,14 linseed, 15,16 castor, 17 canola, 18 palm, 19 safflower 20 and corn oil. 21 The addition of some functional vegetable oils, such as epoxidized corn oil (ECO), can potentially improve the extrinsic and intrinsic properties of ER, while also increasing the biobased content of the final composites.…”
Section: Introductionmentioning
confidence: 99%
“…124 The acrylic groups in POBUA provide C]C linkages to be crosslinked by UV irradiation, which acts as a barrier coating to avoid attacks from corrosive agents on the surface of the mild steel surface. More studies on radiation-curable palm oil-based products have been reviewed by Tajau et al 125 Mu and coworkers reported on the preparation of palm oilbased epoxy resins with recyclability, high mechanical strength, and recongurable shape-memory properties. 126 Initially, palm oil was converted to palm oil-based methyl methacrylate (PMA) monomer by the amidation and esterication method.…”
Section: Polyepoxidesmentioning
confidence: 99%
“…Hydrocarbon resins are formed by oligomerization (thermal, catalytic) of dicyclopentadiene and other components contained in the raw material, such as co-dimers CPD-isoprene, CPD-piperylene or isomers of methyl-dicyclopentadiene or alternative polymeric-based triglycerides and monomers, such as palm oil-based polymeric materials [5]. Sometimes the resins are hydrogenated to improve color (water-free resin) and thermal stability.…”
Section: Dicyclopentadiene Usesmentioning
confidence: 99%